Performance evaluation of broadband service delivery via tethered balloon technology - Alsamhi S.H.; Gupta S.K.; Rajput N.S. (My University, 2025)
New generation of wireless communication technologies gives people more convenience to connect to any wireless communication networks. Nowadays, subscribers want an effective and efficient communication technology which can support services to anyone in anywhere. Moreover, the weakness of terrestrial wireless communication technologies is unable to deliver broadband communication services to satisfy users who are living in thinly populated, remote, rural and hilly areas. Thus, we propose Tethered Balloon technology to provide broadband services, reduce the requirement of terrestrial infrastructure and make available broadband wireless communication connectivity, in thinly populated, remote, rural and hilly areas. We have examined various aspects of Worldwide Interoperability for Microwave Access (WiMAX) broadband service from Tethered Balloon to show the effectiveness of providing the service delivery. Here, broadband service delivery is analyzed and simulated using Optimized Network Engineering Tool (OPNET) Modeler 14.5. The simulation results show significantly the effectiveness of delivering WiMAX via Tethered Balloon technology. © 2016 IEEE.